الخصائص الحركية لامتزاز الفينول على الفحم الفعال المصنع من قشر الجوز (Latakia University Journal -Basic Sciences Series, 2013)
تهدف هذه الدراسة إلى توصيف الظروف التشغيلية لمرشح الفحم الفعال المحضر من قشر الجوز والمنشط كيميائياً بكلوريد الزنك والمفحم عند الدرجة  600Cوذلك بالاعتماد على منحنيات الاختراق. طبقت فرضية انتقال الكتلة (MTZ) بهدف الحصول على تصميم تشغيلي للامتزاز على السرير الثابت والتي تساعد على تحديد متغيرات التشغيل على هذا السرير وذلك عند ثلاثة تراكيز ابتدائية للفينول 20, 40, 60ppm)). درست المتغيرات التشغيلية لعمود الامتزاز بحساب السعة الجزئية لمنطقة انتقال الكتلة F)) وارتفاع منطقة انتقال الكتلة Hz كذلك تم حساب عدد مكافئات الانتقال Nz والكمية الفعلية للفينول التي أزيلت على سرير ثابت من الكربون الفعال عند لحظة الاختراق ABP. The objective of the present work is to determine the operating conditions of an activated carbon filter, based on the characteristics of breakthrough curves. In order to properly design and operate fixed-bed adsorption processes, we apply the concept of the mass transfer zone (MTZ) that helps to obtain the evolutions of the operating parameters of the fixed-bed. Activated carbon is prepared from walnuts crust and activated by impregnating in aqueous zinc chloride solution of wt %(40). Phenol solutions were prepared in three initial concentrations of phenol (20, 40, 60 ppm). The experimental data were analyzed by calculating fractional capacity (F), the height of (MTZ) (HZ), the number of unit transfer equivalent (NZ), the amount of phenol eliminated by the bed of activated carbon at the breakthrough (ABP). The results of the study show that granular sizes (C, D) were more effective than (A, B).